Incidence and Risk Factors of Surgical Site Infections after Abdominal Hysterectomy for Benign Diseases - Punnada Atibovonsuk (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To study incidence and risk factors of surgical site infection (SSI) after abdominal hysterectomy for benign diseases.Materials and Methods: Retrospective study of 82 patients who underwent abdominal hysterectomies for benign diseases between September 2013 and October 2017 at Warinchumrab General Hospital was performed. SSI was defined using the Centers for Disease Control and Prevention criteria. Independent risk factors of SSI after the abdominal hysterectomy were identified by multivariate regression analysis. Results: Incidences of SSI after abdominal hysterectomy was 9.76% (N = 82). There were 8 superficial incisional SSI, no deep incisional and organ-space SSI. Risk factor associated with superficial incisional SSI was a BMI ≥ 23.0 kg/m2 (odds ratio 1.154 [95% confidence interval 1.045-1.274], p = 0.021). Conclusion: Incidence of SSI after abdominal hysterectomy was 9.76% and the significant risk factor in our study was BMI ≥ 23.0 kg/m2